2018
DOI: 10.1515/jbcpp-2017-0221
|View full text |Cite
|
Sign up to set email alerts
|

Proline supplementation mitigates the early stage of liver injury in bile duct ligated rats

Abstract: BackgroundProline is a proteinogenic amino acid with multiple biological functions. Several investigations have been supposed that cellular proline accumulation is a stress response mechanism. This amino acid acts as an osmoregulator, scavenges free radical species, boosts cellular antioxidant defense mechanisms, protects mitochondria, and promotes energy production. The current study was designed to investigate the effect of proline treatment on the liver in bile duct ligated (BDL) rats as an animal model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 62 publications
1
35
0
Order By: Relevance
“…Samples were incubated at 37 °C (5 min, in the dark). Finally, the absorbance of developed color was measured (λ = 595 nm, EPOCH plate reader, BioTek ® Instruments, Highland Park, USA) (Alía et al., 2003; Heidari et al., 2019c).…”
Section: Methodsmentioning
confidence: 99%
“…Samples were incubated at 37 °C (5 min, in the dark). Finally, the absorbance of developed color was measured (λ = 595 nm, EPOCH plate reader, BioTek ® Instruments, Highland Park, USA) (Alía et al., 2003; Heidari et al., 2019c).…”
Section: Methodsmentioning
confidence: 99%
“…However, this research indicated monosaccharides of black beans, including α ‐arabinose, α ‐galactose may be also related to hepatoprotective effect. It is reported that the hepatoprotection provided by proline might be related to attenuating oxidative stress 57 . There are studies which showed that some flavonoids had liver protective activity, 58 flavonoids like daidzein and genistein also could ameliorate effect on CCl 4 ‐induced oxidative stress in the livers of rats 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have mentioned the positive effects of antioxidants against cholestasis [84][85][86]. N-acetyl cysteine, proline, α-lipoic acid, betaine, selenium, glycine, boldine, agmatine, and several other agents have been used to ameliorate cholestasis-induced organ injury [42,62,73,[87][88][89][90][91][92].…”
Section: Discussionmentioning
confidence: 99%